The politics of protection the limits of humanitarian action - Ferris, Elizabeth G. (Washington, D.C. Brookings Institution Press, 2011)
"Examines the evolution of the international community's understanding and commitment to the concept of 'humanitarian protection,' focusing on the inconsistencies inherent in responses from Rwanda to Katrina in order to demonstrate the challenges and limitations of protecting future vulnerable populations from war and natural disasters"--Provided by publisher.
Humanitarian principles and international law -- Human rights and protection -- Protection and humanitarian assistance : communities and governments -- The UN and NGOs in humanitarian operations -- Global governance -- Humanitarian dilemmas -- Natural disasters and protection -- Paying for protection : humanitarian financing -- Future challenges for humanitarian actors -- Concluding observations and recommendations.
Keywords: Humanitarian intervention; Humanitarian assistance